The Evolutionnary Changes in the Nephridial System of Pherettima Kinberg, 1867 (Oligochaeta, Megascolecidae) - Bai, Thai Tran (VNU Journal of Science: Natural Sciences and Technology; Vol 18 No 1, 2002)
Abstract